REVOLUTIONIZING STERILE SUPPLY CHAINS A MULTIDIMENSIONAL APPROACH TO CSSD OPTIMIZATION THROUGH STAKEHOLDER INSIGHT, SMART TECHNOLOGIES AND GLOBAL STANDARDS (The Research of Medical Science Review, 2025)
Background: The Central Sterile Supply Department (CSSD) is vital for ensuring the sterility of medical instruments and equipment, thereby enhancing patient safety and infection control. Optimizing CSSD processes is essential to reduce hospital-acquired infections (HAIs) and improve efficiency. However, challenges such as human error, inconsistent compliance with international guidelines, logistical bottlenecks, and outdated tracking methods persist. Objective: This study aims to revolutionize CSSD optimization by integrating stakeholder insights, smart technologies, and adherence to global standards. The goal is to enhance operational efficiency, minimize HAIs, and ensure a reliable and cost-effective healthcare system. Methodology: A mixed-methods approach was adopted, involving qualitative and quantitative methodologies. Data collection included surveys, questionnaires, interviews, focus groups, and case studies. The target population comprised CSSD managers, healthcare workers, technology providers, policymakers, and accreditation bodies. Quantitative data were analyzed using statistical methods, while qualitative data underwent thematic analysis. Results: The study revealed significant advancements in CSSD operations, including improved service efficiency, equipment management, and staff professionalism. Key interventions included the replacement of noisy trolley wheels, implementation of double-check systems, increased buffer stock, and establishment of an on-call supply system. These measures led to a drastic reduction in supply shortages and enhanced the quality of sterile items. Compliance with personal protective equipment (PPE) protocols improved significantly, and staff behavior and communication saw marked enhancements. Conclusion: Optimizing CSSD operations requires a multifaceted strategy that integrates stakeholder insights, smart technologies, and adherence to global standards. This holistic approach enhances operational efficiency, patient safety, and continuous improvement, ultimately transforming CSSD into a cornerstone of modern healthcare excellence.